Correlation between Self-Control and Cyberbullying Behavior - Azmi, Cici Adelia; Netrawati, Netrawati (Universitas Negeri Padang, 2023)
this the research is motivated by the phenomenon of the development of information technology making cyberspace a place for acts of online violence such as cyberbullying. Cyberbullying is a bad phenomenon that has negative implication for someone and is also a form of bullying. Self-control is one that influences online violence or cyberbullying. This study aims to reveal the relationship between self-control and cyberbullying behavior. This type research is quatitative using method of correlational description analysis. The research sample consisted of 137 students who were selected using the proportional stratified random sampling technique. The intruments used were self-control questionnaires and cyberbullying behavior scale model. The data was processed using the pearson produsct moment correlation hasd formula. The research revealed that (1) the self-control possessed students is the medium category (2) the cyberbullying possessed students is the medium category and (3) there is significant negative relationship between self-control and cyberbullying behavior.